المسؤولية الجزائية للجريمة الإلكترونية - علي، فليحة حسن (الجامعة العراقية - مركز البحوث والدراسات الإسلامية, 2024)
إذا كان للتقدم التقني واستخدام الحاسب الآلي والإنترنت مزايا وإيجابيات، فإن له- كما هو شأن كل الاكتشافات والاختراعات الجديدة- مشاكل وسلبيات أحد مظاهره ظهور صور جديدة من الجرائم لم تكن معروفة في الماضي، وظهور مشاكل قانونية وفقهية منها فكرة المجرم المعلوماتي الذي بمقدوره استخدام وسائل التقنية الحديثة أن يتوصل إلى أنظمة الحاسب الآلي في أي مكان في العالم، وكذلك فكرة المال المعلوماتي (غير المادي) المتمثل في البرامج والمعلومات والبيانات أيا كان موضوعها، كل ذلك أدى إلى تعدد الجهود المبذولة سواء على الصعيد الدولي أو المستوى الإقليمي؛ فعلى الصعيد الدولي عقدت الأمم المتحدة العديد من المؤتمرات لمواجهة الجرائم الإلكترونية وإصدار الكثير من التوصيات، ففي المؤتمر السابع للأمم المتحدة الخاص بمكافحة الجريمة ومعاملة المجرمين أشار المؤتمر إلى جرائم الحاسب الآلي والصعوبات المتعلقة بها باعتبارها من الجرائم المتعدية الحدود ذات الطابع الاقتصادي، وفي أغسطس عام ١٩٩٥ عقد المؤتمر الثامن لمكافحة الجريمة ومعاملة المجرمين في هافانا وكانت الجريمة الإلكترونية والاهتمام بمكافحتها وملاحقتها أحد الموضوعات التي تم بحثها من خلال ندوة أقيمت لهذا الغرض، كما دعت الوكالات والمؤسسات ذات الطابع الدولي إلى التدخل لحماية المعلومات وعدم الاعتداء عليها، وفي مقدمة هذه الوكالات منظمة التنمية والتعاون الاقتصادي. If technical progress and the use of computers and the Internet have advantages and positives, it - as is the case with all new discoveries and inventions - has problems and negatives. One of its manifestations is the emergence of new forms of crimes that were not known in the past, and the emergence of legal and jurisprudential problems, including the idea of the information criminal who is able to use technical means. The modern ability to access computer systems anywhere in the world, as well as the idea of informational money (intangible) represented by programmes, information and data, whatever their subject, all of this has led to multiple efforts made, whether at the international or regional level. At the international level, the United Nations held many conferences to confront cybercrime and issue many recommendations. In the Seventh United Nations Conference on Combating Crime and Treating Criminals, the conference referred to computer crimes and the difficulties related to them as a cross-border crime of an economic nature. In August 1995, the conference was held The eighth to combat crime and treat criminals in Havana. Cybercrime and the interest in combating and prosecuting it was one of the topics that were discussed during a symposium held for this purpose. It also called on agencies and institutions of an international nature to intervene to protect information and not attack it, and at the forefront of these agencies is the Organization for Economic Cooperation and Development.
Keywords: تكنولوجيا الحاسبات -- الجرائم الإلكترونية -- قانون العقوبات -- المسؤولية الجنائية